Short Text Messages Gateway-Based Expert System for Diagnosis of Skin Disease - Hafid, Afdhil; Hasanuddin, Hasanuddin; Ismail, Muhammad (Fakultas Sains dan Teknologi UIN Imam Bonjol Padang, 2021)
Skin disease is the most common infectious disease in people of all ages. In Indonesia, skin diseases are mostly caused by bacterial, fungal, parasitic, and allergic basic diseases. This is different from western countries which are more influenced by degenerative factors. Apart from differences in causes, other factors such as climate, habits and environment also contribute to differences in the clinical picture of skin diseases. Health service policy is one of the main components. Improving good services should not stop with the development of good infrastructure, or only to the examination or diagnosis of doctors for patients, but good health care also lies in how to do it so that people can get health services easily. Cases of ineffective health services often occur in the community, ranging from slow hospital services, practice malls, to a common problem, namely the queuing process that must be carried out by prospective patients who are going to a general practitioner or specialist. In improving the service, you want to develop a problem using the system. the system to be developed is a system that will adopt expert knowledge into a server or also known as an expert system. The expert system to be built will be based on Short text messages or SMS (Short Message Service). This system provides SMS sending services from a website or server to a cellphone number, either free or for a fee. Technology like this is called the SMS Gateway.